Activating 2D nano-kaolinite using hybrid nanoparticles for enhanced phosphate capture. Issue 82 (1st October 2018) - Wei, Yanfu; Yuan, Peng; Song, Yaran; Liu, Dong; Losic, Dusan; Tan, Daoyong; Chen, Fanrong; Liu, Hongchang; Du, Peixin; Zhou, Junming
Abstract : A natural 2D kaolinite host is activated by hybridizing with adsorptive La-based nanoparticles, demonstrating efficient phosphate capture. Abstract : A synergistic host–guest coupling is exploited to disorder nano-kaolinite unit layers to form Al2 O3 nanoparticles, which act as activated adsorptive sites; meanwhile, the coupling enables La-based nanoparticles to anchor homogenously on the nano-kaolinite surfaces, fully utilizing their adsorption ability. The activated hybrid nanostructures exhibit an excellent phosphate adsorption capacity.